Targeting extracellular vesicles‐mediated hepatic inflammation as a therapeutic strategy in liver diseases. (13th July 2020) - Yang, Dakai; Liu, Jing
Abstract: Extracellular Vesicles (EVs) are nano‐ to micro‐sized membranous vesicles that can be produced by normal and diseased cells. As carriers of biologically active molecules including proteins, lipids and nucleic acids, EVs mediate cell‐to‐cell communication and execute diverse functions by delivering their cargoes to specific cell types. Hepatic inflammation caused by virus infection, autoimmunity and malignancy is a common driver of progressive liver fibrosis and permanent liver damage. Emerging evidence has shown that EVs‐mediated inflammation as critical player in the progression of liver diseases since they shuttle within the liver as well as between other tissues with inflammatory signals. Therefore, targeting inflammatory EVs could represent a potential therapeutic strategy in liver diseases. Moreover, EVs are emerging as a promising tool for intracellular delivery of therapeutic nucleic acid. In this review, we will discuss not only recent advances on the role of EVs in mediating hepatic inflammation and present strategies for targeted therapy on the context of liver diseases but also the challenging questions that need to be answered in the field.